A call for implementing preferred practices for brain injury screening in youth to improve transition. - Nagele, Drew A.; McCart, Melissa; Hooper, Stephen R.; DePompei; Glang (NeuroRehabilitation, 2018)
BACKGROUND: It is vital to engage in systematic screening to identify and serve children who may have sustained an acquired brain injury (ABI) - either traumatic or non-traumatic, so they can be successfully transitioned between environments and life stages. This is particularly important for children and adolescents given the impact an ABI can have on learning and social functioning over the course of the neurodevelopmental process. A pattern of repeated, undiagnosed mild brain injuries may lead to mood or behavior disorders, learning problems. Despite increasing awareness of brain injury as a public health issue, there has not been implementation of systematic screening practices in schools or other public health settings similar to other conditions (e.g., vision disorders, Autism Spectrum Disorders). OBJECTIVES: What is needed to address this lack of systematic screening for ABI is a rationale for systematic screening for ABI in children and adolescents, including examining successful models of screening for other disorders and conditions. METHODS: A review was conducted of available ABI screening methods, including a description of the available screening tools for pediatric ABI, along with supporting research findings. RESULTS: A comparison was made of these pediatric ABI screening tools, looking at the purpose of the tool, the populations and settings in which the tool can be used, the time and cost for administering the tool, the evidence basis in the literature supporting the tool, and the types of outcomes that can be attained from using the tool. CONCLUSION: Recommendations are made for procedures for systematically implementing ABI screening in pediatric settings including schools, primary care providers, mental health, and juvenile justice systems to improve the access to brain injury services and affording more successful transition of adolescents into the adult roles.